Democracy in Timor-Leste and the power of the vote - Hercus Pereira dos Santos (Journal of Adat Recht, 2025)
Democracy comes from the Greek word’s demos and kratos. Demos means people and kratos means power. Therefore, democracy means power is in the hands of the people. Power comes from the people and the people as the holder of power. Even though the word democracy is a foreign word in Timor-Leste that originates from Latin, but in practice, the Timorese have practiced democracy for most of their lives since the times of the ancestors. Since the rule of the clan, the village, the suco and even the kingdom usually happened with the consent of its people. The people delegated power to the data; the nobles; and then these data were to choose a village chief, a suco chief, and even a liurai (king, ruler) of a kingdom. Even family and community matters, decisions were made through a consensus, a dialogue called nahe biti boot. This reality shows that the Timorese have practiced democracy since ancient times where power is not only in the hands of one person but in the hands of a set of important people in that system itself known as an aristocratic republic. Democracy today also happens in the same way. The people delegate their power to the village chiefs, suco chiefs, the members of the national parliament (hence forming the government) and the president of the republic through votes; of the election. This means that the votes of the people are extremely important in determining the life of a so-called democratic state like Timor-Leste. Democracy must coexist in harmony with the state legal system, that is, democracy must be regularized through state legal norms. Nothing is absolutely free in the world because freedom without responsibility can make it debauchery as long as there are no state legal norms to regulate. Today's modern state must be a democratic state of law, the state that recognizes the power of the people, that is, the state that recognizes that the people as the holder of power, and this democratic state must be regulated through state legal norms, and these state legal norms must recognize that state power resides in the people and in the name of the people, because the people as the sole holder of power. This article aims to deal with the power of voting in relation to democracy where we can see that in a democratic state, important decisions are made through votes. The method of this research is a qualitative method of observation and analysis of the documents linked to the theme treated. With this study we are able to see how voting has power in democracy. We have seen that voting is very important to ensure the proper functioning of democracy and we can say that democracy has to do with votes or in a summarized way we can call it a democracy of votes. We can conclude that any democratic state must promote and value the vote through a transparent, free, direct, secret process, that is, the voting process must at least respect the seal of the vote to guarantee the freedom of voters.